Computing patient-specific hemodynamics in stented femoral artery models obtained from computed tomography using a validated 3D reconstruction method. (January 2020) - Colombo, Monika; Bologna, Marco; Garbey, Marc; Berceli, Scott; He, Yong; Rodriguez Matas, Josè Felix; Migliavacca, Francesco; Chiastra, Claudio
Highlights: Automatic segmentation of patient-specific femoral arteries from computed tomography. 3D reconstruction of patient-specific femoral artery models from computed tomography. In-vitro validation of the reconstruction method using stented 3D printed phantoms. Impact of boundary conditions on the hemodynamics of patients' femoral artery models. Abstract: Patients with peripheral artery disease who undergo endovascular treatment are often inflicted by in-stent restenosis. The relation between restenosis and abnormal hemodynamics may be analyzed using patient-specific computational fluid dynamics (CFD) simulations. In this work, first a three-dimensional (3D) reconstruction method, based on an in-house semi-automatic segmentation algorithm of a patient's computed tomography (CT) images with calcification and metallic artifacts, and thrombus removal is described. The reconstruction method was validated using 3D printed rigid phantoms of stented femoral arteries by comparing the reconstructed geometries with the reference computer-aided design (CAD) geometries employed for 3D printing. The mean reconstruction error resulting from the validation of the reconstruction method was 6% in both stented and non-stented regions. Secondly, a patient-specific model of the stented femoral artery was created and CFD analyses were performed with emphasis on the selection of the boundary conditions. CFD results were compared in scenarios with and without common femoral artery bifurcation, employing flat or parabolic inlet velocity profiles. Similar helical flow structures were visible in all scenarios. Negligible differences in wall shear stress (<0.5%) were found in the stented region. In conclusion, a robust method, applicable to patient-specific cases of stented diseased femoral arteries, was developed and validated.